Health Promotion Through Counseling and Literary Interventions: Media to Increase Breastfeeding Mothers’ Well-Being - Wattimena, Inge; Hapsari, Elisabet Widyaning (ANIMA Indonesian Psychological Journal, 2012)
The WHO target of achieving 80% success rate of breastfeeding mothers for a minimum of 6 months has not been met, so a program had been performed on 105 pregnant and post-delivery women through counseling and literary interventions. Six months after delivery they were traced back and a questionnaire of three open ended questions was sent by mail to them. A total of 45 women responded to the questionnaire. They were asked about the benefits of the interventions, the prosperity enjoyed, and of suggestions to encouraged breastfeeding behavior. The answers were qualitatively analyzed. Results showed that after the interventions, they got more under- standing, motivated, and happy. They experienced physical, psychological, and social well-beings. Unfortunately medical teams and the community were not fully participating yet in encouraging mothers to breastfeed. It is recommended to promote breastfeeding through competent moti-vators for the welfare of families and nation. Target WHO agar 80% ibu menyusui minimal 6 bulan belum tercapai, sehingga perlu dilakukan upaya melalui intervensi penyuluhan dan materi bacaan. Promosi dilakukan pada 105 ibu hamil dan pasca-melahirkan. Kelompok ini ditelusuri kembali setelah 6 bulan melahirkan. Kepada mereka ditanya per surat tiga pertanyaan terbuka tentang manfaat intervensi, kesejahteraan yang dinikmati melalui ASI, dan saran untuk menggalakkan pemberian ASI. Sebanyak 45 ibu yang menyampaikan jawabannya. Jawaban dianalisis melalui metode kualitatif deskriptif. Hasil menunjukkan bahwa para ibu mendapat manfaat dari intervensi, semakin mengerti, termotivasi, dan bahagia. Mereka menikmati kesejahteraan fisik, psikis, maupun sosial. Di pihak lain diutarakan bahwa belum sepenuhnya tim medis maupun masyarakat berpartisipasi dalam menggalakkan ASI. Disarankan agar masalah ASI disosialisasikan ke masyarakat luas melalui para motivator yang kompeten, untuk kesejahteraan keluarga dan bangsa.